KAJIAN PRAGMATIK BAHASA IKLAN DAN PEMANFAATANNYA BAGI PEMBELAJARAN BAHASA INDONESIA DI SMA - Aditya Pratama (Universitas Sultan Ageng Tirtayasa, 2021)
The rapid development of communication needs have enabled language also experienced significant developments in terms of delivery.Language is not only conveyed face-to-face, but language containing certain information is conveyed through the mass media.One example of information delivery through mass media, is advertising. Advertising is used to convey a message to manufacturers about a particular product or service with the aim of influencing the public so that they are interested in buying the products or services offered.These ads form the image of the advertised product. In the creation of advertisements, manufacturers try to convey a message to consumers in the form of a meaningful symbol, namely language.However, so far the language used as a means of communication in advertising has its own meaning, so that some people will not directly understand the meaning of the advertisement.This can be influenced by the form of advertising design expressed in various ways in order to achieve the target to be targeted.Based on this, the use of varied advertising language is interesting to research.By utilizing the development of pragmatic science, this paper seeks to describe the use of advertising language and its implementation as teaching materials for writing in high school.